Characterization β-carotene content of eight cultivars of carrot (Daucus carota L.) and its relation to the color - Ventrera, Nancy Beatriz; Vignoni, Lucía; Alessandro, María Soledad; Césari, Matilde; Césari, Ricardo; Guinle, Viviana; Giménez, Adriana; Tapia, Olga (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
The aim was to determine, eight commercial cultivars such as 'Flakkee' cultivated at INTA (National Institute of Agricultural Technology), Experimental Station La Consulta during two years, according to β-carotene content and its relationship with Color Index (CI). An experimental design with blocks at random with 3 replications was used. β-carotene was evaluated (spectrophotometry at 450 nm) and calculated the CI, by capture of digital image with PC and scanner, measuring L, a and b of CIELAB system. The results were analyzed by principal components analysis (PCA) and visualization of variability by mean of data mapping, analysis of variance, test of mean difference and correlations. The contents of β-carotene and the IC of cultivars remained constant during the two years studied, resulting Natasha, Flakesse and Colmar the ones with the greatest nutritional value in terms of contribution of β-carotene. In the range of values under 18 mg%g of β-carotene, we observed a significant positive correlation in the Supreme, Spring and Laval cultivars. It was found no significant high lineal correlation between the IC and β-carotene content. It is appropriate the use of color index to predict, in a range of values, β-carotene content in carrot cultivars.